DNA-methylation eraser TET2 activates WTIP expression to suppress an AKT-dependent chemoresistance of gastric cancer - Yan Guo; Hongyang Yu; Jinyang Li; Kewei Liu; Mengyi Han; Yuxin Tang; Li Su; Xianfeng Li; Haixia Wu; Dongfeng Chen (Neoplasia: An International Journal for Oncology Research)
Chemoresistance is one of the major causes of the failure in gastric cancer (GC) treatment and leads to poor clinical outcomes. Ten-eleven translocation (TET) 2 expression and activity are frequently reduced in solid tumors. However, whether TET2 participants in GC chemoresistance remains poorly understood. In this study, we demonstrated that the TET2 acts as a novel suppressor of GC chemoresistance. TET2 and transcription factor PATZ1 work together to promote the expression of WTIP. WTIP interacts with PP2A to inhibit the T308 phosphorylation and kinase activity of AKT, thereby suppressing stemness and chemoresistance of GC. Thus, the novel TET2-WTIP transcriptional axis, which is frequently silenced, suppresses an AKT-dependent chemoresistance of GC. TET2, combined with WTIP and AKT-pT308, can synergistically serve as a biomarker for predicting chemotherapy response in GC patients. Furthermore, we highlight that combining AKT inhibitor with chemotherapy is a promising therapeutic strategy for TET2-silenced GCs with chemoresistance in clinic.